LTR retrotransposons transcribed in oocytes drive species-specific and heritable changes in DNA methylation - Julie Brind’Amour (Nature Portfolio, 2018)
De novo DNA methylation during mouse oogenesis occurs within transcribed regions. Here the authors investigate the role of species-specific long terminal repeats (LTRs)-initiated transcription units in regulating the oocyte methylome, identifying syntenic regions in mouse, rat and human with divergent DNA methylation associated with private LITs.